Drones and UAVs for Methane Emissions Detection, Monitoring, and Regulatory Compliance - Nash, Susan Smith (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
New developments in drones and unmanned aerial systems (UAS) can enable operators to comply with new methane emissions regulations from the Environmental Protection Agency which took effect in August 2016, and those from the Bureau of Land Management which took effect in November 2016. The new regulations contain specific monitoring and reporting requirements for different types of oil and gas operations, from upstream production facilities to midstream processing and transportation. This paper reviews the requirements, and examines current solutions, including various types of drones and sensors. In addition, the paper discusses how to go about planning drone flights, given the different types of installations to be monitored and the legal restrictions in place.